Test Scheduling of SoC by using Dynamic Voltage Frequency Scaling (DVFS) Technique - Hassan, Hasliza (Emerging Advances in Integrated Technology, 2022)
High temperature gradients in System on Chip (SoC) lowered the performances, reliability and leakage power. In addition, temperature during testing gain more compared to normal operation. Therefore, the investigation of the impact dynamic voltage frequency scaling (DVFS) on the thermal aware test scheduling performance will be the main contribution of this work. The test scheduling algorithm which embeds frequency scaling effect with dynamic voltage supply is tested on ITC’02 benchmark. The formulation of ILP is to minimize the group of the test session in SoC and continued with DVFS formulation. Compared to the conventional thermal-aware scheduling approach based purely on a frequency scaling, this technique provides shorter overall test times and greatly improved flexibility to satisfy strict thermal constraints. The proposed DVFS with thermal aware task scheduling allows to minimize test time more than 46%.